Possible Mechanisms by Which Enzymatic Degradation of Human Serum Albumin Can Lead to Bioactive Peptides and Biomarkers - Kragh-Hansen, Ulrich (Frontiers in Molecular Biosciences, 2018)
Partial enzymatic degradation of human serum albumin in vivo can lead to the generation of peptides with novel functions or to peptides that might serve as biomarkers for disease. In pathological conditions, biomarkers are possibly produced from the protein in the lysosomes and set free by cell death, or cell death could release acid endoproteases which produce biomarkers by degrading extracellular albumin. Alternatively, lysosomes or secretory granules can be stimulated to release enzymes which produce bioactive peptides from albumin. In physiological conditions, it is proposed that bioactive peptides can be made by enzymatic attack on the protein bound to the endosomal neonatal Fc receptor. The peptides formed could leave the cell, together with native albumin, by exocytosis. Thus, the receptor could have a new function in addition to saving albumin from degradation in the lysosomes. Large amounts of albumin are degraded every day, and this fact can compensate for the short in vivo half-lives of the bioactive peptides. One or more of the procedures outlined above could also apply to other plasma proteins or to structural proteins.